Safe engagement in physical activity through pre-exercise risk assessment: an observational study at a single facility over 16 years - Akihiro Hirata; Akihiro Hirata; Yoshifusa Takao; Tomoaki Seto; Satoshi Kurose; Yoshinobu Saito; Yoshinobu Saito; Shinji Sato; Shigeki Tsuzuku; Yuko Oguma; Yuko Oguma (Frontiers in Public Health)
BackgroundRegular and appropriate physical activity has health benefits; however, to ensure safety, a pre-exercise medical check based on health information is important. In this study, we aimed to clarify the relationship between risk classification by physicians at a health promotion facility in Japan and the occurrence of adverse events during facility use.MethodsWe evaluated 3,571 individuals, excluding those with an unknown sex, age, medical assessment of exercise limitations, and facility usage status. Based on the results of the medical checkups conducted by a physician, the participants were divided into an exercise-prohibited group and an exercise-permitted group (exercise-permitted group, subdivided into non-restricted, orthopedic-restricted, internal medical-restricted, and combined-restricted groups). The risk of adverse events was examined.ResultsThe group in which exercise was prohibited comprised 72 participants, and that in which exercise was permitted comprised 1935, 612, 456, and 496 participants in the non-restricted, orthopedic-restricted, internal medical-restricted, and combined-restricted groups, respectively. Logistic regression analysis was performed on the four subgroups of the exercise-permitted group, and the odds ratios for adverse events adjusted for individual attributes were 1.04 [95% confidence interval (CI), 0.59–1.84; p = 0.89], 0.97 (95% CI, 0.53–1.78; p = 0.93), and 0.80 (95% CI, 0.42–1.54; p = 0.51) for the orthopedic-restricted, internal medical-restricted, and combined-restricted groups, respectively. A power analysis revealed that the study had a high level of power (0.99), based on a Cox–Snell R2 of 0.05 and a sample size of 3,499, indicating sufficient sensitivity to detect differences between groups.ConclusionNo significant difference in the odds of adverse events was found regardless of the presence or absence of exercise restrictions. Therefore, despite exercise-related risks, pre-exercise screening can help ensure that exercise is performed as safely as it is by individuals without such risks. However, further discussion is required regarding the necessity of screening for all exercise participants.